International legal contracting: the need for and Importance of its harmonization in a globalized world - Carreño Bernal, Emmanuel Guillermo (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
In the current legal frameworks shaped by globalization, where international commercial transactions have become a prevailing trend, participants in international trade face significant challenges, particularly concerning the legal framework governing international contractual relationships. In response, this research article examines the process of harmonizing cross-border contract law and explores the use of various instruments derived from this process as effective and suitable mechanisms to address –or at least substantially mitigate– these challenges, thereby promoting greater legal certainty in international trade.